Frontline demonstrations on Indian mustard (Brassica juncea) for showcasing production potential and economics in hot sub humid (moist) eco-region: FRONTLINE DEMONSTRATIONS ON INDIAN MUSTARD FOR PRODUCTION POTENTIAL AND ECONOMICS - R N MEENA; KAMLESH MEENA; RAJNEESH SRIVASTVA; ASHVIN KUMAR MEENA; R P SHARMA; R N PRASAD; JAGDISH SINGH (Journal of Oilseeds Research, 2020)
The production ofIndianmustard (Brassica juncea) islower due to non-adoption ofrecommended high yielding varieties and improved technologies by the farming community in eastern plains of Uttar Pradesh, India. To educate farmers on the improved technologies, 92 frontline demonstrations (FLDs) were conducted in farmers' fields by KVK, Deoria, Uttar Pradesh, India. The technologies demonstrated included improved varieties, thinning, irrigation, date of sowing, seed treatment, spacing, balanced use of fertilizers, intercultural operations and plant protection measures. The improved technology showed increase in the yield of mustard between 22.3-43.3% over local checks. Technology gap was highest in Pusa Jaikisan (1767 kg/ha) and lowest in Pusa Bold (341 kg/ha) variety. The extension gap was highest with Pusa Jaikisan (447 kg/ha) and lowest with Pusa Bold (434 kg/ha). Technology index was highest (50.5%) with Pusa Jaikisan and lowest (13.9 %) with Pusa Bold. Lower, values of technology index indicates higher feasibility of the technology in eastern plains of Uttar Pradesh.